Investigation of phenol adsorption on macroporous polymeric adsorbents - Aleksandra M. Tasić; Ignjatović Ivana D. Sredović; Aleksandra B. Nastasović (Zaštita Materijala)
This work reports results on phenol adsorption from aqueous solution by porous copolymers based on glycidyl methacrylate: two samples of macroporous crosslinked poly(glycidyl methacrylate-co-ethylene glycol dimethacrylate), were synthetized by suspension copolymerisation with ethylene glycol dimethacrylate. In addition, the two copolymer samples were functionalized with ethylene diamine. The amounts of adsorbed phenol were presented in the form of adsorptions isotherms, which were interpreted using Langmuir, Freundlich and Sips' equations. The first was found to express high level of agreement with experimental data. Phenol adsorption indicate the homogeneous distribution of active sites present on the investigated polymers. It was found that adsorption of phenol on copolymers is fast and depends on the presence of amino groups and on the pore size. From the obtained results, it was possible to distinguish macroporous polymer as a material which possesses the capacity for adsorption of phenol comparable to that of activated carbon.